Fungal asthma among Ugandan adult asthmatics. (4th May 2021) - Kwizera, Richard; Bongomin, Felix; Olum, Ronald; Meya, David B; Worodria, William; Bwanga, Freddie; Fowler, Stephen J; Gore, Robin; Denning, David W; Kirenga, Bruce J
Abstract: Fungal sensitization is associated with poor asthma control. We aimed to determine the prevalence and factors associated with fungal asthma among Ugandan adults. Individuals aged ≥18 years with a new diagnosis of asthma in the last 12 months participating in the African Severe Asthma Program constituted the study population. Skin prick test results, clinical and demographic data were retrieved from the database, and serum Aspergillus fumigatus specific antibodies and total IgE were measured in stored blood. We enrolled 374 patients, median (IQR) age 34 (25–45) years, 286 (76.5%) females and 286 (76.5%) with severe asthma. Prevalence of Aspergillus fumigatus sensitization was 42.0% (95% CI: 37.1–47.0%), allergic bronchopulmonary aspergillosis (ABPA) 3.2% (1.8–5.5%), severe asthma with fungal sensitization (SAFS) 16% (12.7–20.1%) and allergic bronchopulmonary mycosis (ABPM) 2.9% (1.7–5.2%). Older age (55–64 years) (crude odds ratio (cOR) = 2.6), sensitization to at least one allergen (cOR = 9.38) and hypertension (cOR = 1.99) were significantly associated with Aspergillus sensitization, whereas tertiary education level (cOR = 0.29), severe depression (cOR = 0.15) and strong emotions (cOR = 0.47) were not. High occupational exposure to Aspergillus (cOR = 4.26) and contact with moulds (cOR = 14.28) were significantly associated with ABPA. Palpitations (cOR = 5.54), uncontrolled asthma (cOR = 3.54), eczema/dermatitis (cOR = 3.07), poor lung function (cOR = 2.11) and frequent exacerbations (cOR = 1.01) were significantly associated with SAFS. Eczema/dermatitis (cOR = 1.55) was significantly associated with ABPM, but cold weather trigger (cOR = 0.24) was not. Fungal asthma is a significant problem among Ugandans with asthma and should be particularly considered in individuals who remain uncontrolled despite optimal standard of care for asthma, as it is responsive to available and affordable oral antifungal therapy. Lay Summary: This study showed that fungal asthma is a significant problem among Ugandans with asthma with a high prevalence. Fungal asthma should be considered in patients with uncontrolled asthma despite receiving optimal standard of care. This is the first modern attempt to define these endotypes of asthma in Africa.